2002
DOI: 10.1002/clc.4950250706
|View full text |Cite
|
Sign up to set email alerts
|

T‐peak to T‐end interval may be a better predictor of high‐risk patients with hypertrophic cardiomyopathy associated with a cardiac troponin i mutation than qt dispersion

Abstract: SummaryBackground: Patients with hypertrophic cardiomyopathy (HCM) associated with a deletion of lysine 183 (K183del) in the cardiac troponin I (cTnI) gene suffer sudden cardiac death at all ages. However, the correlation between QT variables and sudden cardiac death in these patients remains uncertain.Hypothesis: We evaluated the correlation between QT variables and sudden cardiac death and/or ventricular tachyarrhythmia (SCD/VT) in patients with HCM associated with the cTnI mutation.Methods: We analyzed 10 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
186
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 226 publications
(201 citation statements)
references
References 19 publications
8
186
1
Order By: Relevance
“…ESR Sercan Okutucu et al, Prolonged Tp-e and Tp-e/QT in systemic sclerosis this ratio is being used increasingly more frequently as an electrocardiographic index of ventricular arrhythmogenesis in various diseases. Previous studies have shown that prolongation of the Tp-e interval is associated with increased mortality in Brugada syndrome, hypertrophic cardiomyopathy, and in patients undergoing primary percutaneous coronary intervention for myocardial infarction [13,22,23]. Yamaguchi et al [24] found that the Tp-e/QT ratio is a superior predictor of torsades de pointes than either QTc interval or QTd in patients with long QT syndrome (LQTS).…”
Section: Discussionmentioning
confidence: 99%
“…ESR Sercan Okutucu et al, Prolonged Tp-e and Tp-e/QT in systemic sclerosis this ratio is being used increasingly more frequently as an electrocardiographic index of ventricular arrhythmogenesis in various diseases. Previous studies have shown that prolongation of the Tp-e interval is associated with increased mortality in Brugada syndrome, hypertrophic cardiomyopathy, and in patients undergoing primary percutaneous coronary intervention for myocardial infarction [13,22,23]. Yamaguchi et al [24] found that the Tp-e/QT ratio is a superior predictor of torsades de pointes than either QTc interval or QTd in patients with long QT syndrome (LQTS).…”
Section: Discussionmentioning
confidence: 99%
“…Tp-e/ QT and Tp-e/QTc are relatively new markers which also indicate repolarization defects. Published studies clearly suggest the applicability of Tp-e/QT ratio as a potentially important index of arrhythmogenesis, both under the conditions of short, normal and long QT interval, as well as in congenital and acquired channelopathies, in various high-risk populations, such as, patients with long QT syndrome [19], hypertrophic cardiomyopathy [20], post-myocardial infarction [21], inducible ventricular tachycardia [24,25], repaired tetralogy of Fallot [26] or Brugada syndrome [27], Tp-e interval had been found to be more prolonged than control patients. Underlying mechanism of Tp-e prolongation and ventricular repolarization abnormality was proposed by Antzelevitch and coworkers [18].…”
Section: Discussionmentioning
confidence: 99%
“…Prolongation of this interval represents a period of potential vulnerability to re-entrant ventricular arrhythmias [17,18]. Prolonged Tp-e has been associated with increased risk of mortality in the congenital and acquired long QT syndromes [19], hypertrophic cardiomyopathy [20] and also in patients undergoing primary PCI for myocardial infarction [21]. However, there is a lack of literature about utilization of Tp-e in HD patients.…”
mentioning
confidence: 99%
“…26 The TpTe/QT ratio was calculated as the ratio of TpTe in that lead to the corresponding QT interval. 25,30,31 HR, RR, PR, and QRS intervals were also measured. QTd was calculated as the difference between the longest and shortest individual lead QTc.…”
Section: Methodsmentioning
confidence: 99%